2014
DOI: 10.7314/apjcp.2014.15.1.391
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Associations between Genetic Polymorphisms in GSTM1, GSTT1 and GSTP1 and Pancreatic Cancer Risk: A Multi-Institutional Case-Control Study in Japan

Abstract: Background: We aimed to evaluate the role of genetic polymorphisms in tobacco carcinogen-metabolizing genes and their interactions with smoking in a hospital-based case-control study of Japanese subjects. Materials and Methods: We examine the associations of pancreatic cancer risk with genetic polymorphisms in GSTM1, GSTT1 and GSTP1, phase II enzymes that catalyze the conjugation of toxic and carcinogenic electrophilic molecules. The study population consisted of 360 patients and 400 control subjects, who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Analysis on connection of GSTs (glucotransferases, mu GSTM1 , pi GSTP1 and theta GSTT1 , group of detoxification genes) considered an association between the null-genotype of GSTT1 gene and increased risk of PC in Asians but no in Caucasians, Africans or Japanese 44-46.…”
Section: Nuclear Dna Changesmentioning
confidence: 99%
“…Analysis on connection of GSTs (glucotransferases, mu GSTM1 , pi GSTP1 and theta GSTT1 , group of detoxification genes) considered an association between the null-genotype of GSTT1 gene and increased risk of PC in Asians but no in Caucasians, Africans or Japanese 44-46.…”
Section: Nuclear Dna Changesmentioning
confidence: 99%
“…Finally, 85 articles (19,604 cases and 23,710 controls) were kept (Fig. 1), of which 70 articles (16,131 cases and 19,696 controls) were about the relationship between GSTM1 and cancers [4,5,16,17,24–89] (Table 1); 49 articles (11,555 cases and 14,606 controls) were about the relationship between GSTT1 and cancers [4,5,16,24,25,27–31,33,34,36–39,41,42,44–49,51,52,56,58,60,61,63,65–68,70,74–76,79,80,82–85,87,88,90–93] (Table 2); and 31 articles (8518 cases and 9884 controls) were about GSTP1 and cancers [5,16,17,24,30,31,34,36,42,44,45,47,49,52,59,66,67,70,79,88,94–103] (Table 3) among smokers. Among these researches, 8 articles mentioned the classification of smoking levels (20 pack-year).…”
Section: Resultsmentioning
confidence: 99%
“…Subgroup results demonstrated that alcohol consumption might increase the cancer risks of GSTM1-null carriers among Caucasians with a 2.873-fold, but no association was found among Asians. Subgroup results also showed that drinking increased cancer Li [71] 2008 Asian He [72] 2008 Asian Chen [73] 2008 Asian Xie [74] 2008 Asian Boccia [75] 2007 Caucasian Gastric cancer Agorastos [76] 2007 Caucasian Cervical cancer Qian [77] 2006 Asian Wang [78] 2006 Asian Huang [4] 2006 Mixed Peters [79] 2006 Caucasian Head and neck cancer Shao [80] 2006 Asian Qiao [81] 2005 Asian Tamer [5] 2005 Caucasian Gastric cancer Gelatti [82] 2005 Caucasian Liver cancer Alexandrie [83] 2004 Caucasian Lung cancer Ravina [84] 2003 Caucasian Lung cancer Risch [85] 2003 Caucasian Laryngeal cancer Wang [86] 2002 Asian Zheng [87] 2002 Deek [24] 2021 Mixed Pathak [27] 2021 Tcheandjieu [28] 2020 Mixed Ritambhara [34] 2019 Caucasian Lung cancer HB 120 Rostami [30] 2019 Caucasian Chronic myeloid leukemia Yamashita [31] 2019 Asian Kalacas [33] 2019 Rodrigues-Fleming [36] 2018 Boccia [38] 2015 Pan [41] 2014 Silva [42] 2014 Mixed Upper aerodigestive tract cancer Jiang [44] 2014 Asian Yamada [45] 2014 Shukla [48] 2013 Berber [49] 2013 Caucasian Prostate cancer Kang [51] 2013 Asian García-González [52] 2012 Caucasian Gastric cancer Liu [56] 2012 Asian Rouissi [61] 2011 Caucasian ...…”
Section: Quantitative Synthesis 321 the Relationship Between Gstm1 Po...mentioning
confidence: 99%
“…ROS) by the oxidative Phase I enzymes, which are mainly alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH) and cytochrome P-450 enzymes (CYPs). Phase II conjugating enzymes, such as glutathione-S-transferase (GST), act usually as inactivating enzymes that inactivate carcinogens (Zakhari, 2013, Yamada et al, 2014.…”
Section: Alcohol Metabolism Through Xenobioticsmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) are a multi-gene family of phase-II metabolic enzymes. The conjugation of reduced glutathione is catalyzed by GSTs enzymes with a variety of endogenous and exogenous electrophilic compounds, including several potentially toxic carcinogens and chemotherapeutic drugs (Yamada et al, 2014), thereby reducing the reactivity of the compounds by making them water soluble and favouring their elimination from the body.…”
Section: Alcohol Metabolism Through Xenobioticsmentioning
confidence: 99%